Bandwidth enhanced CPW fed elliptical wideband antenna with slotted defected ground structure - T P Madhav, B; Purna Kishore, M (International Journal of Engineering and Technology, 2018)
In this article, a simple curved elliptical coplanar wave guide fed antenna is proposed for wideband applications. An elliptical shaped model of multiband antenna is converted as notch band antenna with placement of slots in the radiating structure and by incorporating defected ground structure, bandwidth enhancement isattained in the proposed model. In short, the multiband antennais modelled in to wideband antenna with bandwidth of 17.8 GHz and impedance bandwidth of 67%.By placing defected ground structure adjacent to feed line on the ground plane, additional resonant frequencies are raised and enhancement in the bandwidth is obtained. The measured results are providing excellent correlation with simulation results obtained from HFSS and CST tools.